Patient Perspectives Important for Medical Devices - Nichols, Emma Hitt (MD Conference Express, 2015)
In this session, presenters focused on patient perspectives in the context of clinical trials, patient-reported outcomes, and regulatory science in the medical device industry. Presenters discussed collaborative research, centers that evaluate medical devices, patient surveys, and patient preferences in nephrology.